2009
DOI: 10.1016/j.bpj.2008.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Defibrillation in Human Cardiac Tissue: A Simulation Study

Abstract: We aim to assess the effectiveness of feedback-controlled resonant drift pacing as a method for low energy defibrillation. Antitachycardia pacing is the only low energy defibrillation approach to have gained clinical significance, but it is still suboptimal. Low energy defibrillation would avoid adverse side effects associated with high voltage shocks and allow the application of implantable cardioverter defibrillator (ICD) therapy, in cases where such therapy is not tolerated today. We present results of comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…8,9 Arguably, should SW reentry be regulatable by procedures other than DC shocks or those combined with low-energy shocks, it could lead to innovative therapeutic modalities for prevention of arrhythmic death. Although several conceptual approaches have been proposed to terminate SW reentry by low-energy DC application, e.g., resonant drift, 10,11 controlling chaos, 12 synchronized pacing, 13,14 and unpinning of SWs, 15,16 feasibility of these approaches has not yet been validated. In isolated rabbit hearts, we have previously shown that moderate hypothermia facilitates termination of VT through destabilization (unpinning) of SW reentry.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Arguably, should SW reentry be regulatable by procedures other than DC shocks or those combined with low-energy shocks, it could lead to innovative therapeutic modalities for prevention of arrhythmic death. Although several conceptual approaches have been proposed to terminate SW reentry by low-energy DC application, e.g., resonant drift, 10,11 controlling chaos, 12 synchronized pacing, 13,14 and unpinning of SWs, 15,16 feasibility of these approaches has not yet been validated. In isolated rabbit hearts, we have previously shown that moderate hypothermia facilitates termination of VT through destabilization (unpinning) of SW reentry.…”
Section: Introductionmentioning
confidence: 99%
“…Bidomain theory [21] provides an approach to how stimulation from electrodes in or near the heart can excite and pace the myocardium, or defibrillate via the induction of virtual electrodes [22] . These theories have been used to design [23] and test methods to produce defibrillation by repetitive trains of small amplitude electrical stimuli, numerically [24,25] , in vitro, on cell cultured preparations and isolated perfused hearts, and in acute animal preparations [8, 26 -27] .…”
Section: Featured Review Journal Of Atrial Fibrillationmentioning
confidence: 99%
“…Even though the implementation and use of these models is a complex and difficult task, the applications and benefits justify their use. Computer models have been used during the tests of new drugs, development of new medical devices, and new techniques of noninvasive diagnosis for several cardiac diseases …”
Section: Introductionmentioning
confidence: 99%
“…Computer models have been used during the tests of new drugs, development of new medical devices, and new techniques of noninvasive diagnosis for several cardiac diseases. [1][2][3] To speed up cardiac simulations and to allow more precise and realistic ones, 2 different techniques have been traditionally exploited: parallel computing and sophisticated numerical methods. [4][5][6] These 2 research areas, parallel computing and numerical methods, are continuously evolving at a fast pace.…”
Section: Introductionmentioning
confidence: 99%